Humic acid-phosphate fertilizer interaction and extractable phosphorus in soils of contrasting texture (Revista Ciência Agronômica, 2023)
Extractable phosphorus (P) in soil depends on soil test employed, reactivity of fertilizer and interaction of Padded to the soil properties, including organic matter. The aim of this paper was to assess the contents of P extracted from RedLatosol (LVd) and Quartzarenic Neosol (RQ) samples, incubated with 0; 5; 10; 50 or 100 mg kg-1 C-humic acid (C-HA) and400 mg kg-1 of P, via Araxá phosphate rock (AP), Bayóvar reactive phosphate rock (BP) or single superphosphate (SS). Thus,it was adopted a five (C-HA concentrations) x three (P sources) factorial arrangement, using a randomized block design withthree replications. The mixtures of soil, C-HA concentrations and P sources were incubated for 60 days; in sequence, the soil Pwas extracted by solutions of Bray-1, Mehlich-1 and Mehlich-3 and mixed ion exchange resin. In the LVd and RQ samples, theaddition of C-HA reduced extractable phosphorus when the source was AP and BP. The levels of extractable P increased withthe application of C-HA in RQ when the source was SS; the average concentration of 50 mg kg-1 C-AH provided the maximumextractable P by Bray-1, Mehlich-3 and mixed resin. The pH is the chemical attribute that most influence the extractable Pcontent of the soil.